Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20112797
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean and MIND Diets Containing Olive Biophenols Reduces the Prevalence of Alzheimer’s Disease

Abstract: The risk of Alzheimer’s disease (AD) increases with nonmodifiable conditions including age and lack of effective efficacious pharmacotherapy. During the past decades, the non-pharmacotherapy mode of treatment of dietary modification received extensive attention in AD research. In order to reduce the AD pathology and cognitive decline, various dietary patterns have been attempted including caloric restriction (CR), dietary approaches to stop hypertension (DASH), ketogenic diets (KD), Mediterranean diet (MedDi) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 131 publications
0
35
1
1
Order By: Relevance
“…This eating pattern forces the system to shift from glucose metabolism toward the metabolism of fatty acids with the consequent production of ketone bodies. Despite the increasing availability of preclinical and clinical scientific evidence regarding the nonpharmacological approach in the prevention of neurodegeneration, a review paper describing the current knowledge, differences, and similarities of underlying mechanisms and the exerted effects of these two nutritional approaches on cognitive function is still missing [22]. Another open issue regards the impact of these dietary patterns on specific populations characterized by clinical frailty, which have been demonstrated to be at higher risk to develop AD-related cognitive impairment, such as those individuals with diabetes [26], chronic kidney disease [27], and other chronic-degenerative disorders associated with the aging process [28,29].…”
Section: Mediterranean Diet Ketogenic Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…This eating pattern forces the system to shift from glucose metabolism toward the metabolism of fatty acids with the consequent production of ketone bodies. Despite the increasing availability of preclinical and clinical scientific evidence regarding the nonpharmacological approach in the prevention of neurodegeneration, a review paper describing the current knowledge, differences, and similarities of underlying mechanisms and the exerted effects of these two nutritional approaches on cognitive function is still missing [22]. Another open issue regards the impact of these dietary patterns on specific populations characterized by clinical frailty, which have been demonstrated to be at higher risk to develop AD-related cognitive impairment, such as those individuals with diabetes [26], chronic kidney disease [27], and other chronic-degenerative disorders associated with the aging process [28,29].…”
Section: Mediterranean Diet Ketogenic Dietmentioning
confidence: 99%
“…Data from recent studies show that reducing the intake of trans-fat and saturated fats, (e.g., red and processed meats); decreasing the consumption of dairy products; and increasing intake of fruits, vegetables, legumes, and whole grains could be associated with the improvement of cognitive function and prevention of AD [19,20]. Moreover, it has been suggested that different eating patterns, including Mediterranean diet (MedDi), Ketogenic Diet (KD), caloric restriction, Dietary Approaches to Stop Hypertension (DASH), and Mediterranean-DASH diet Intervention for Neurological Delay (MIND), could possibly reduce the pathophysiological hallmarks of AD [19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An emerging dietary pattern of interest is the MIND diet, which combines aspects of the MeDi and DASH diet with an emphasis on dietary components linked to neuroprotection and dementia prevention [166][167][168]. For example, the MIND diet has a more explicit emphasis on dietary components with polyphenolic effects, such as blueberries, red wine, and dark chocolate [169]. The MIND diet has been associated with a lower incidence of neurocognitive decline [150,168,170] and ADRD [169][170][171][172].…”
Section: Mediterranean-dash (Mind) Dietmentioning
confidence: 99%
“…For example, the MIND diet has a more explicit emphasis on dietary components with polyphenolic effects, such as blueberries, red wine, and dark chocolate [169]. The MIND diet has been associated with a lower incidence of neurocognitive decline [150,168,170] and ADRD [169][170][171][172]. Indeed, recent evidence suggests that the MIND dietary pattern is associated with more protective effects when compared to either the MeDi or DASH directly [165][166][167].…”
Section: Mediterranean-dash (Mind) Dietmentioning
confidence: 99%